Growth, Structure, Spectroscopy, and Laser Operation of a “Mixed” Yb:(Y,Lu)3Al5O12 Garnet Crystal - Sami Slimi; Pavel Loiko; Mingyan Pan; Pauline Lehoux; Venkatesan Jambunathan; Martin Smrz; Tomas Mocek; Yicheng Wang; Weidong Chen; Valentin Petrov; Rosa Maria Solé; Magdalena Aguiló; et al. (Crystals, 2023)
A single crystal of ytterbium-doped “mixed” yttrium–lutetium aluminum garnet with a stoichiometric composition of (Y0.601Lu0.233Yb0.166)3Al5O12 was grown by the Czochralski method and its structure, vibronic, spectroscopic, and laser properties were studied. The stimulated-emission cross-section for Yb3+ ions was maximized to 2.53 × 10−20 cm2 at 1031 nm. The emission bandwidth was ~8 nm, and the reabsorption-free luminescence lifetime of the 2F5/2 state was 1.063 ms. Pumped at 941 nm, the Yb laser generated a maximum output power of 1.04 W at 1.03 and 1.05 μm with a high slope efficiency of 76.4% and a laser threshold of 76 mW. A continuous wavelength tuning over a range of 51.6 nm (1026.4–1078.0 nm) was also achieved. Power scaling was achieved using a 969 nm diode-pumped microchip cavity. A maximum output power of ~9 W was obtained at 1.05 μm with a slope efficiency of 76% and an almost circular laser beam profile.